The Performance of IPO in Iran: Empirical Test of Some Related Factors - S.H. Alavi Tabari; A. Rahmani; SH. Maki (مطالعات تجربی حسابداری مالی, 2008)
This study has investigated the IPOs’ long-term performance, in Tehran Stock   Exchange. The purpose of this study was to examining if IPOs underperform in long-term.  Furthermore,    this  study   has  investigated    the effects  of some  features  of IPO  firms on IPOs’ long-term  performance   (e.g. size  and  profitability   of  the  firm  before  the  IPOs, ownership   structure   and IPOs'  short-term   returns  ). The sample   included   143 IPOs in Tehran Stock Exchange   from 1376 to 1386. The results show that IPOs in Tehran Stock Exchange   under-performs    in long-run.   There   is a negative   and significant relationship   between   size and the profitability of the firms before the IPO and IPOs' long-run performance. State-ownership and structure of ownership have no effects on long-term performance. Finally, there is no relationship between short-term return and long-term performance of IPOs.